How to develop self-confidence and influence people by public speaking - Carnegie, Dale. (India : Mini books publishers, 2004)
"... Offers hundreds of practical and valuable tips on influencing the important people in your life: your friends, your customers, your business associates, your employers"--Cover, P. [4].
Keywords: Public speaking; Communication